Comparing bio-tribocorrosion of selective laser melted Titanium-25% Niobium and conventionally manufactured Ti-6Al-4 V in inflammatory conditions - Chakkravarthy, Vijayavarman; Manojkumar, Palanivel; Lakshmanan, M.; Eswar Prasad, Korimilli; Dafale, Rucha; Chitra Vadhana, V.; Narayan, Ramasubramanian L. (Elsevier, 2023)
The present study aims to evaluate the biocompatibility and bio-tribocorrosion potential of selective laser melted (SLM) Titanium-25% Niobium (Ti-25 Nb) alloy. Further the suitability of the Ti-25 Nb implant was assessed by benchmarking with conventionally manufactured commercial Ti-6Al-4 V implant. Ball-on-plate tests were performed on these alloys while submerging them in an acidic sodium lactate (ASL) medium. Simultaneously, the open circuit potential (OCV) of the two alloys were measured before, during and after sliding the indenter. Characterization of the surface morphology and composition after the test revealed that SLM fabricated Ti-25 Nb exhibits superior wear resistance and hence has greater resistance to depassivation than commercial Ti-6Al-4 V implant. Biocompatibility of the implants, in terms of cell adhesion, cell proliferation, osteogenic differentiation and Alkaline Phosphatase (ALP) activity were also studied on the surfaces of the worn alloys. Results indicate that the worn Ti-25 Nb surface is more conducive for the healthy growth of cells and facilitates more pronounced ALP activity than that of Ti-6Al-4 V, over a duration of 14 days. The superior bio-tribocorrosion performance and biocompatibility of Ti-25 Nb is attributed to SLM induced development of compressive residual stresses, smoother worn surface, higher compactness of the Nb oxides over the alloy surface and negligible toxicity of Nb.
Keywords: Additive manufacturing; Bio-tribocorrosion; Titanium-Niobium alloy; Bio-toxicity; Metal oxidative stress